Percepatan Penurunan Stunting Melalui Konseling Keluarga dan Pemberian Makanan Tambahan Pada Balita Stunting - Andi Sitti Umrah; Ummi Kalsum Marwan; Patmahwati; Sri Rahayu Amri; Juliani; Andi Kasrida Dahlan; Ayu Pertiwi; Melinda (Forum Kerjasama Pendidikan Tinggi, 2024)
Stunting is a condition where growth disorders in children are closely related to inadequate nutritional intake. Stunting is currently the focus of health problems faced at global, national and local levels, so fast and responsive treatment is needed to overcome this. Based on WHO data, around 21.9% of toddlers or around 149 million children under five experience stunting throughout the world and in Indonesia around 21.6% in 2022. Meanwhile, Indonesia has set a target for the prevalence of stunting to decrease to 14% in 2024. The aim of this community service is to determine the sanitary condition of the family environment as one of the factors causing stunting in toddlers; 2) to determine the effectiveness of the counseling and PMT program on stunted toddlers, in terms of increasing the weight and height of stunted toddlers in Palopo City. This activity was carried out in Palopo City in 2 (two) places, namely Takkalala and Binturu sub-districts. The number of participants was 14 toddlers and their families. The method used is specific intervention through PMT using local food and sensitive intervention through family counseling using digital media. The results of community service show that the factor that drives stunting in the city of Palopo is poor sanitation in the family environment. Providing counseling to families and local food PMTs has had a positive impact on accelerating the reduction of stunting, which is indicated by a significant increase in TB and BW in children under five after being given the intervention. It is hoped that this activity can be increased and continued in monitoring and evaluation activities for intervention to reduce stunting in the city of Palopo.